Does Fiscal Policy Matter for the Trade Account? : A Panel Cointegration Study - Nickel, Christiane (IMF Working Papers; Working Paper ;, 2006)
This paper analyzes the empirical relationship between fiscal policy and the trade account. Research prior to this paper did not consider that the components of private and public demand in the import demand equation exhibit different elasticities. Using pooled mean group estimation for annual panel data of the G-7 countries for the years 1970 through 2002, we provide empirical evidence that the composition of overall demand-i.e., the distribution among public demand, private demand, and export demand-has an impact on the magnitude of the trade account deficit.